(untitled) (Journal of Partial Differential Equations, 2003)
" We study the structure of solutions to the interface problems for second order quasi-linear elliptic partial differential equations in two dimensional space. We prove that each weak solution can be decomposed into two parts near singular points, a finite sum of functions in the form of cr^03b1 log^m r03c6(03b8) and a regular one w. The coefficients c and the C^1,03b1 norm of w depend on the H00b9-norm and the C^00ba,000b03b1-norm of the solution, and the equation only."